Academic Information System for Student Leave at the National University: Academic Information System for Student Leave at the National University - Ary Dwi Pantoro; Ucuk Darusalam; Ben. Rahman (Institute of Computer Science (IOCS), 2020)
Limitations regarding the leave application process at the national university students tend to be effective and efficient because it still uses a manual system that makes students feel difficult. Since the number of files that accumulate leave so as to make the part of academic administration forgot to process when there are students who ask leave of absence. The purpose of this design will generate student leave application program is web based, so as to provide convenience to the user in filing and processing leave. Software system development methods using Waterfall Model. The results of this study will show the main page there is also a facility to leave application, as well as leave application status changes. Through this website, students can leave application process online.